Komitmen Terhadap Kelompok Sebagai Kontinuitas Bullying di Kalangan Remaja (Studi Kasus Sekolah X, Kampar) - Arfandi, Muhammad Rizki; A, Askarial (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to explore the role of commitment to the group in maintaining the continuity of bullying behavior among adolescents at School X, Kampar. The main focus of this research is to understand how solidarity, loyalty, and social pressure within a group or gang influence individuals in engaging in bullying. The research method used is a qualitative approach with data collection techniques including in-depth interviews and observations. The informants in this study include students, guidance and counseling teachers (BK), and the school principal. The findings show that commitment to the group significantly contributes to strengthening bullying behavior. Adolescents involved in certain gangs or groups often feel pressured to conform to behaviors that are considered group norms, including bullying, even though they are aware of its negative impacts. The fear of being ostracized and the need to show loyalty to the group drive them to continue engaging in such behavior. Furthermore, the high solidarity within the group is often misinterpreted as a duty to remain loyal, even to actions that are harmful. This research suggests the importance of collective awareness-based interventions to reduce bullying behavior, including involving all parties (students, teachers, and parents) in creating a more inclusive and empathetic school environment.